2019
DOI: 10.1186/s12909-019-1851-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between students’ perception of the educational environment and their subjective happiness

Abstract: Background: Happiness, a subjective judgment about one's quality of life, is influenced by environmental factors and should be considered as an important goal of medical education, which should support each learner's development as a person as well as a professional. However, although several studies have reported on the correlation between Dundee Ready Educational Environment Measure (DREEM) scores and students' academic achievement, few have investigated the relationship between DREEM scores and students' su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
(79 reference statements)
3
16
0
6
Order By: Relevance
“…This presumption may resonate with our setting, where feedback over the years suggests that pre-clinical students perceive their learning experience more positively than their seniors. Yoo and Kim [ 16 ] however, argue that there exists no universal tendency in changes of student perceptions towards the educational environment as the course progresses.…”
Section: Discussionmentioning
confidence: 99%
“…This presumption may resonate with our setting, where feedback over the years suggests that pre-clinical students perceive their learning experience more positively than their seniors. Yoo and Kim [ 16 ] however, argue that there exists no universal tendency in changes of student perceptions towards the educational environment as the course progresses.…”
Section: Discussionmentioning
confidence: 99%
“…One factor, among others, that is expected to act as a push to the students' agripreneurial interest in Nigeria is the exposure to entrepreneurship education early in 100 and 200 levels. However, the impact of this exposure, measured by subjective happiness and/or fulfilment, is expected to be contingent on the quality of learning and quality of teachers available for the students [54]. According to [55], mentoring is regarded as one of the best tools for "reducing stress for novice teachers, orientation to curriculum and promoting the creation of better norms of collegiality and collaboration".…”
Section: Apriori Expectationsmentioning
confidence: 99%
“…Therefore, mentorship was expected to have a positive effect on the students' likelihood to become an agripreneur. More scholars are positive that the age, gender, number of the graduates in the family, size of the family, cumulative grade point average (CGPA) is among other variables that provide positive and statistically significant influence on their subjective happiness triggered by entrepreneurial and career intentions [54], [31], [58].…”
Section: Apriori Expectationsmentioning
confidence: 99%
“…Previous studies have reported that social self-perception influences the subjective happiness (SH) of medical students [ 13 ]. Happiness is defined as “a global evaluation of life satisfaction,” and happiness is often referred to as subjective well-being [ 14 ].…”
Section: Introductionmentioning
confidence: 99%